A facile and rapid route to synthesize ceria-zirconia nanoparticles with high performance for CH3SH decomposition. (September 2017) - Liu, Feng; He, Dedong; Lu, Jichang; Chen, Dingkai; Liu, Pan; Yu, Jie; Liu, Jiangping; Wan, Gengping; He, Sufang; Luo, Yongming
Graphical abstract: Highlights: Ceria-zirconia nanoparticles were rapidly prepared by urea grind combustion method. An improvement of catalytic activity was observed for Ce0.8 Zr0.2 O2 prepared by this method. More oxygen vacancies and surface chemisorbed oxygen attributed to improved catalytic activity. No report on ceria-zirconia solid solution for CH3 SH catalytic decomposition can be found. Abstract: A novel and facile route was employed to rapidly synthesize ceria-zirconia nanoparticles with high-performance for CH3 SH catalytic decomposition. Compared with classical surfactant-assisted method, the modified urea grind combustion (UGC) method offered advantages of easy operation and time-saving. An improvement of catalytic activity for CH3 SH decomposition was observed for Ce0.8 Zr0.2 O2 nanoparticles prepared by this method. The synthesized materials were characterized by nitrogen adsorption-desorption, XRD, Raman, TEM, UV-vis, H2 -TPR and XPS. Combined with those results, it was found that increased concentration of oxygen vacancies and surface chemisorbed oxygen species were formed in Ce0.8 Zr0.2 O2 nanoparticles prepared by this UGC method, thus improving reducibility and catalytic activity of the catalyst. In addition, the used catalysts have been characterized to understand the reaction processes during CH3 SH catalytic decomposition.